Programmatic assessment design choices in nine programs in higher education - Baartman, Liesbeth; van Schilt-Mol, Tamara; van der Vleuten, Cees (Frontiers in Education, 2022)
In programmatic assessment (PA), an arrangement of different assessment methods is deliberately designed across the entire curriculum, combined and planned to support both robust decision-making and student learning. In health sciences education, evidence about the merits and pitfalls of PA is emerging. Although there is consensus about the theoretical principles of PA, programs make diverse design choices based on these principles to implement PA in practice, fitting their own contexts. We therefore need a better understanding of how the PA principles are implemented across contexts – within and beyond health sciences education. In this study, interviews were conducted with teachers/curriculum designers representing nine different programs in diverse professional domains. Research questions focused on: (1) design choices made, (2) whether these design choices adhere to PA principles, (3) student and teacher experiences in practice and (4) context-specific differences between the programs A wide range of design choices were reported, largely adhering to PA principles but differing across cases due to contextual alignment. Design choices reported by almost all programs include a backbone of learning outcomes, data-points connected to this backbone in a longitudinal design allowing uptake of feedback, intermediate reflective meetings and decision-making based on a multitude of data-points made by a committee and involving multi-stage procedures. Contextual design choices were made aligning the design to the professional domain and practical feasibility. Further research is needed in particular with regard to intermediate-stakes decisions.